76.4k views
2 votes
Solve the equation below algebraically for the exact value of x. 6 − 23(x + 5) = 4x

User PxDav
by
5.4k points

2 Answers

5 votes
6-23(x+5)=4x

6-23x-115=4x

-109=27x

x=4.03

Solve the equation below algebraically for the exact value of x. 6 − 23(x + 5) = 4x-example-1
User Fableal
by
4.1k points
6 votes

Answer:

See below.

Explanation:

6 - 23(x+5) = 4x

First, distribute.

6 - 23x - 115 = 4x

Reorder the terms.

6 - 115 - 23x = 4x

Subtract.

-109 -23x = 4x

Add 23x to both sides.

-109 = 27x

Divide by 27.

x = -109/27 (This cannot be simplified)

User Photosynthesis
by
5.0k points